Multi-Omics Analysis of Gut Microbiota and Sperm Quality in Tibetan Breeding Boars - Mingxuan Zhao; Mengjia Han; Hongliang Zhang; Xiangdong Wang; Yikai Yin; Jian Zhang; Peng Shang (Metabolites)
Background/Objectives: Reproductive efficiency in breeding boars critically impacts swine industry productivity, with sperm quality being multifactorially regulated by gut microbiota. This study aimed to elucidate the microbiota–metabolite interactions underlying sperm quality differences in Tibetan boars. Methods: Integrated 16S rRNA sequencing and untargeted metabolomics were performed on fecal and semen samples from eight healthy Tibetan boars (31–33 months old), stratified into low-semen (CJ) and high-semen utilization (HJ) groups. Analyses included sperm quality assessment, microbial profiling, and metabolic pathway enrichment. Results: The HJ group exhibited significantly enhanced sperm motility and semen utilization rates (p < 0.05). Gut microbiota composition differed markedly, with Firmicutes and Proteobacteria enriched in HJ boars. Metabolomics identified key metabolites positively correlated with sperm quality (e.g., butyrate, phenyllactic acid), while lithocholic acid showed negative associations. KEGG analysis revealed predominant involvement in butanoate metabolism and bile acid biosynthesis. Core microbiota (e.g., Ruminococcus) modulated sperm quality through short-chain fatty acid networks and bile acid homeostasis. Conclusions: Gut microbiota regulated the sperm microenvironment via a “metabolic-immune” dual pathway mediated by the gut–testis axis. These findings establish a theoretical basis for probiotic or metabolite-targeted strategies to improve boar reproductive performance.